Flap-Based Reconstruction in Patients with Autoimmune Disease: An Institutional Experience with the Deep Inferior Epigastric Perforator Flap and Review of the Literature - Manasyan, Artur; Stanton, Eloise W.; Moshal, Tayla; Daar, David A.; Carey, Joseph N.; Koesters, Emma (Journal of Reconstructive Microsurgery, 2024)
Background Autoimmune diseases are associated with characteristic chronic inflammation, aberrations in tissue perfusion, and hypercoagulability, and thus have considerable implications for local and free-flap reconstruction. We seek to summarize the current evidence on outcomes of flap-based reconstruction in patients with pre-existing autoimmune disease and present our experience with autologous breast reconstruction in this population.Methods PubMed, Embase, Scopus, Cochrane, and Web of Science were searched for relevant articles, and pertinent data were presented qualitatively. Institutional data were queried for patients who underwent autologous breast reconstruction with deep inferior epigastric perforator (DIEP) flaps between 2015 and 2024. A retrospective review was conducted to identify DIEP patients with a history of autoimmune disease. Data on patient demographics, medication history, flap outcomes, and perioperative complications were collected.Results The majority of existing studies found no increased independent risk of flap complications. However, other complications, predominantly wound dehiscence, were independently associated with autoimmune disease. Regarding immunosuppressant therapy, the literature demonstrated that perioperative glucocorticoid use was consistently associated with all complications, including seroma, infection, wound disruption, and partial flap loss.Our 13-patient institutional experience identified no cases of total flap loss or microvascular thrombotic complications. There was one case of partial flap necrosis further complicated by abdominal site cellulitis, and one case of recipient-site dehiscence managed with local wound care. No patients required re-operation for flap or donor-site complications.Conclusion The literature suggests that flap reconstruction can be performed safely in patients with autoimmune conditions, which was also supported by our institutional experience. While there is likely minimal risk of microsurgical complications in the context of free tissue transfer, donor-site morbidity and wound dehiscence remain major concerns for patients with a history of autoimmune disease. Limiting the use of immunosuppressive agents, especially corticosteroids, may potentially improve outcomes of flap reconstruction.
Keywords: flap; autoimmune; microsurgery; reconstruction